多汗症的二级护理管理. (17th September 2018) - Wade, R.; Llewellyn, A.; Jones‐Diette, J.; Wright, K.; Rice, S.; Layton, A.M.; Levell, N.J.; Craig, D.; Woolacot, N.
Abstract : Linked Article:  Wade et al. Br J Dermatol 2018;179 :599–608